Sense of agency at a gaze-contingent display with jittery temporal delay - Kim, Junhui; Yoshida, Takako (Frontiers in Psychology, 2024)
Inconsistent jittery temporal delays between action and subsequent feedback, prevalent in network-based human–computer interaction (HCI), have been insufficiently explored, particularly regarding their impact on the sense of agency (SoA). This study investigates the SoA in the context of eye-gaze HCI under jittery delay conditions. Participants performed a visual search for Chinese characters using a biresolutional gaze-contingent display, which displayed a high-resolution image in the central vision and a low-resolution in the periphery. We manipulated the delay between eye movements and display updates using a truncated normal distribution (μ to μ + 2 σ) with μ ranging from 0 to 400 ms and σ fixed at 50 ms. Playback of recorded gaze data provided a non-controllable condition. The study revealed that both reported authorship and controllability scores, as well as the fixation count per second, decreased as μ increased, aligning with trends observed under constant delay conditions. The subjective authorship weakened significantly at a μ of 94 ms. Notably, the comparison between jittery and constant delays indicated the minimum value (μ) of the distribution as a critical parameter influencing both authorship perception and visual search time efficiency. This finding underscores the importance of the shortest delay in modulating SoA. Further examining the relative distribution for fixation duration and saccade amplitude suggests an adaptation in action planning and attention distribution in response to delay. By providing a systematic examination of the statistical attributes of jittery delays that most significantly affect SoA, this research offers valuable implications for the design of efficient, delay-tolerant eye-gaze HCI, expanding our understanding of SoA in technologically mediated interactions. Moreover, our findings highlight the significance of considering both constant and variable delay impacts in HCI usability design, marking a novel contribution to the field.